India’s State-Level Energy Efficiency Implementation Readiness - Sarkar, Ashok; Mukhi, Neha; Padmanaban, Padu S.; Kumar, Amit; Kumar, Kulbhushan; Bansal, Manoj; Das, Shyamasis; Ganta, Shuboday; Verma, Anurag (World Bank, Washington, DC, 2017)
India is currently one of the fastest growing major economies in the world. Sustaining a high growth rate is believed to be critical for India to alleviate poverty in the country, since it feeds more than a billion people. Energy, being a key enabler of a country’s economic growth and development, has witnessed a significant rise in its consumption in India. In 2013 about 528.34 million tons of oil equivalent (Mtoe) were consumed, making India the third largest consumer of energy in the world, more than 70 percent of which is supplied by fossil sources. Increasing energy demand naturally strains the country’s resources and impacts the environment. This warrants decoupling the country’s economic growth and energy demand. This is also echoed through India’s intended nationally determined contribution submitted in the run-up to the Paris Climate Conference, where the government has highlighted energy conservation as a key mitigation strategy. It seeks to achieve total avoided capacity addition of 19,598 MW and fuel savings of around 23 million tons per year through the National Mission for Enhanced Energy Efficiency (NMEEE). However, this requires concerted effort at the central and state levels, especially considering the existing federal governance architecture where many subjects, including electricity, fall under the jurisdictions of both the center and the state.